Covenant (Clover City, CA Sony Pictures, 2007)
To the students of the Spenser Academy, the Sons of Ipswich are the baddest boys on campus. But that's not all they share. The four friends also share a 300-year-old secret: they're warlocks, the teenage descendants of a 17th-century coven of witches. So when the long-banished fifth son suddenly appears and threatens to kill their loved ones, they realize they must face their enemy in order to prevent him from stealing their powers and shattering the covenant forever.
109130
Keywords: Mystery & Thrillers; Fantasy Films; Horror Films; Supernantural Films; Teenage Films; Magic Films; Witches